Safety and Efficacy of Tirofiban for Acute Ischemic Stroke Patients With Large Artery Atherosclerosis Stroke Etiology Undergoing Endovascular Therapy - Huo, Xiaochuan (Front Neurol, 2021)
Objective: To investigate the safety and efficacy of tirofiban in acute ischemic stroke (AIS) patients with large artery atherosclerosis (LAA) stroke etiology receiving endovascular therapy (EVT). Methods: In this multi-center prospective study, patients who were considered to have an indication received a low dose intra-arterial bolus (0.25–1 mg) of tirofiban. The safety and efficacy outcomes at 90-day follow-ups included symptomatic intracranial hemorrhage (sICH), recanalization rate, functional outcome, and mortality. Results: Among the 649 AIS patients with LAA, those in the tirofiban group (n = 244) showed higher systolic blood pressure (BP) and NIHSS score on admission, puncture-to-recanalization time, lower frequency of intravenous thrombolysis and intra-arterial thrombolysis, higher frequency of antiplatelet, heparinization, mechanical stent retrieval, aspiration, balloon angioplasty, and more retrieval times compared with those in the non-tirofiban group (n = 405) (all P < 0.05). Tirofiban was found to be associated with superior clinical outcomes in anterior circulation stroke and major stroke patients [adjusted odds ratio (OR) = 2.163, 95% confidence interval (CI) = 1.130–4.140, P = 0.02 and adjusted OR = 2.361, 95% CI = 1.326–4.202, P = 0.004, respectively] and a lower risk of mortality at 90-day follow-ups (adjusted OR = 0.159, 95% CI = 0.042–0.599, P = 0.007 and adjusted OR = 0.252, 95% CI = 0.103–0.621, P = 0.003, respectively). There was no significant difference in sICH between the two groups. Conclusions: Tirofiban in AIS patients with LAA undergoing EVT is safe and may benefit the functional outcomes in anterior circulation and major stroke patients and showed a trend for reduced mortality.